2013
DOI: 10.22499/2.6301.012
|View full text |Cite
|
Sign up to set email alerts
|

A global evaluation of fronts and precipitation in the ACCESS model

Abstract: How global precipitation will change in the future is of great socio-economic importance. It is therefore vital that climate models are able to adequately simulate the characteristics of precipitation and the individual precipitation events. Fronts play an important role in providing precipitation and they can be associated with heavy rain and flooding.In this paper the ACCESS1.3 atmosphere model is evaluated in terms of frontal and non-frontal precipitation. An objective front identification method is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Catto et al (2013) found that although rainfall associated with fronts was underestimated, the major precipitation errors were associated with non -frontal rainfall, which might derive from systems such as cutoff lows. Since cutoff lows are important for rainfall across southern Australia, and their decline in number have contributed to the autumn rainfall reduction in the southeast , the poor representation of cutoffs in models (Grose et al, 2012) might explain that, even if the observed autumn rainfall decline is a forced signal and not simply driven by natural variabil ity, models are less likely to capture it.…”
Section: Discussion and Synthesismentioning
confidence: 96%
See 1 more Smart Citation
“…Catto et al (2013) found that although rainfall associated with fronts was underestimated, the major precipitation errors were associated with non -frontal rainfall, which might derive from systems such as cutoff lows. Since cutoff lows are important for rainfall across southern Australia, and their decline in number have contributed to the autumn rainfall reduction in the southeast , the poor representation of cutoffs in models (Grose et al, 2012) might explain that, even if the observed autumn rainfall decline is a forced signal and not simply driven by natural variabil ity, models are less likely to capture it.…”
Section: Discussion and Synthesismentioning
confidence: 96%
“…Frontal systems are very important for rainfall in southern Australia (Berry et al, 2011;Simmonds et al, 2012) particularly in the southeast in autumn (Catto et al, 2012) and the southwest in winter, where they have been found to be declining in number (Hope et al, 2014). Fronts in an example GCM, ACCESS1.3, tend to be well represented in their frequency and the proportion of precipitation associated with them (Catto et al, 2013), although the intensity of that precipitation is underestimated. Frontal systems tend to intensify via a confluence of subtropical and polar jets, and thus the observed and projected large-scale meridional shifts in pressure and the polar jet align with a reduction in the number of fronts impacting upon southern Australia Hope, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Frontal systems are often associated with rainfall, and the strength of this association is of interest in many climatological studies (e.g., Pook et al 2012;Catto et al 2012). To explore this, the rainfall associated with fronts will be assessed in this section.…”
Section: E Cwb Rainfall and Frontsmentioning
confidence: 99%
“…A number of automated algorithms have now been applied to large-scale fields available from reanalyses in order to generate climatologies of fronts [McIntosh et al (2008) for southwest Western Australia, Berry et al (2011a) for the globe, and Simmonds et al (2012) for the Southern Hemisphere]. The ability of these methods to identify fronts from relatively low-resolution data suggests that they can also be applied to climate model output, and this has recently been demonstrated by Catto et al (2013). The focus of the Berry et al and Simmonds et al studies was on the climatologies, whereas here our interest centers on the synoptics of the fronts and their consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Where attention is paid to shorter-term variability, studies have adopted a phenomenological approach, analyzing precipitation associated with synoptic features, such as mesoscale fronts and convective systems (e.g., Brown et al, 2010;Catto et al, 2013;Van Weverberg et al, 2013), or sub-seasonal modes, such as the Madden-Julian Oscillation (MJO; e.g., Hung et al, 2013). Yet the processes that produce precipitation in GCMs -the interactions between the sub-gridscale parameterizations and the resolved dynamicsfunction on the native gridscale and time step of the models, not on a 3 h or daily mean basis or on a regional average.…”
Section: Introductionmentioning
confidence: 99%